Acute-on-chronic liver failure due to hepatitis B - Garg, Pallavi; Madan, Kaushal (Frontiers in Gastroenterology, 2023)
Acute-on-chronic liver failure (ACLF) is a complex health problem with a high short-term mortality. It is a form of end-stage liver disease (ESLD) characterized by acute hepatic insult on the background of an underlying chronic liver disease leading to other extrahepatic organ failures. Due to its rapid rate of progression, it is a challenge for both hepatologists and intensivists to treat. Many variations exist regarding its definition, leading to descriptions of various clinical phenotypes. Patients who have chronic hepatitis B (CHB) or Hepatitis B virus (HBV)-related cirrhosis are also prone to develop hepatic or extrahepatic failures when they develop a superadded insult. Different severity criteria and prognostic scores have been proposed and validated among various populations and various etiologies including HBV. The management mainly focusses on support of various organ failures while waiting for the liver to regenerate, for liver transplantation, or, in the case of HBV-related ACLF (HBV-ACLF), for the anti-virals to take effect. Liver transplantation still remains the definitive treatment for HACLV in general and even for HBV- ACLF. Medical therapies, such as nucleos(t)ide analogue (NUCs)and artificial liver support, may improve survival in a subset of patients with HBV-related ACLF. This review updates the understanding of HBV-ACLF from epidemiological and clinical studies and provides new insights into the definition, diagnostic criteria, epidemiology, pathogenesis, treatment, and prognostication of HBV-ACLF.